2021
DOI: 10.1039/d1cs00240f
|View full text |Cite
|
Sign up to set email alerts
|

Biosensing with DNAzymes

Abstract: This article provides a comprehensive review of biosensing with DNAzymes, providing an overview of different sensing applications while highlighting major progress and seminal contributions to the field of portable biosensor devices and point-of-care diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
198
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(198 citation statements)
references
References 352 publications
0
198
0
Order By: Relevance
“…Although the inputs are designed as hairpin structures, we have demonstrated that transducer components could be introduced, allowing transformation of common biological signals such as miRs into the standard hairpin inputs. Besides miR inputs, the FSM has the potential to incorporate functional moieties on nucleic acids, such as aptamers ( 23 , 49 , 51 ), DNAzymes ( 52 ), therapeutic oligos ( 53 ), reactive chemicals ( 54 ), metal nanoparticles ( 22 ), and proteins ( 24 26 , 36 ) to achieve various formats of molecular inputs and outputs. For example, temporal information of biological molecules involved in diseases could be used to guide drug releases or program functional molecular devices.…”
Section: Discussionmentioning
confidence: 99%
“…Although the inputs are designed as hairpin structures, we have demonstrated that transducer components could be introduced, allowing transformation of common biological signals such as miRs into the standard hairpin inputs. Besides miR inputs, the FSM has the potential to incorporate functional moieties on nucleic acids, such as aptamers ( 23 , 49 , 51 ), DNAzymes ( 52 ), therapeutic oligos ( 53 ), reactive chemicals ( 54 ), metal nanoparticles ( 22 ), and proteins ( 24 26 , 36 ) to achieve various formats of molecular inputs and outputs. For example, temporal information of biological molecules involved in diseases could be used to guide drug releases or program functional molecular devices.…”
Section: Discussionmentioning
confidence: 99%
“…Biosensing is a sub‐field of analytical sensing, which places special attention on incorporating molecular biometric entities in the detection process. [ 151–153 ] The excellent photophysical properties of CDs such as photoluminescence (PL) and good electrical conductivity make them valuable biosensing materials. [ 154–156 ] Generally, the sensing principle of CDs is based on the specific interaction between the surface functional groups or targeting moiety and the analytes, leading to the change of CDs’ optical emission characteristics ( Figure a).…”
Section: Applicationsmentioning
confidence: 99%
“…Biosensing is a sub-field of analytical sensing, which places special attention on incorporating molecular biometric entities in the detection process. [151][152][153] The excellent photophysical properties of CDs such as photoluminescence (PL) and good electrical conductivity make them valuable biosensing materials. [154][155][156] Generally, the sensing principle of CDs is based on the specific interaction between the surface functional groups or targeting moiety and the analytes, leading to the change of CDs' optical CTAC and triethanolamine MSN Provide drug loading sites Cancer cell targeting and drug delivery [276] Pyrene and polyethylenimine Black phosphorus Enhanced NIR absorption Photothermal-chemo combination therapy [267] Citric acid and urea ZIF Carrier for ECL labels and enhancing the ECL signals Biosensor [302] Pyrene and polyethylenimine MXene Marrow-bandgap nanosonosensitizer Sonodynamic therapy [303] Di(Dopa-Se) Hydrogels Self-healing and adhesion properties in vivo cancer detection [304] Figure 4.…”
Section: Biosensingmentioning
confidence: 99%
“…Dzs-based sensors can work as a promising candidate for ion detection in vitro , including Mg 2+ , Ni + , Na + , Zr 2+ , K + , and so on ( Wu et al., 2017 ; Liu et al., 2021b ; Chen et al., 2017 ; McConnell et al., 2021 ; Cheng et al., 2020 , 2021 ; Ren et al., 2020 ). Liu’s group developed a lanthanide-specific Dzs array for the separation of lanthanides from non-lanthanides ( Huang et al., 2016 ).…”
Section: Applications Of Dna-based Enzymatic Systems In Sensing and B...mentioning
confidence: 99%